IMPLEMENTASI LAYANAN KONSELING ISLAMI DI SMA NEGERI 1 TANJUNG TIRAM - Khairiyah Agustina (Pascasarjana UIN Sumatera Utara, 2017)
Abstract :This research is generally aimed to describe Implementation of Islamic CounselingService at Sekolah Menengah Atas Negeri 1 Tanjung Tiram. Specifically, however, this study aims todescribe the implementation of individual Islamic counseling services and group counseling guidance atState Senior High School 1 Tanjung Tiram, with details to describe what issues are addressed throughindividual and group Islamic counseling services, to describe how How to carry out individual Islamiccounseling services and counseling guidance services and any barriers that occur in carrying out individualIslamic counseling services and group counseling services. The type of research used in this thesisuses qualitative research and the approach is done using naturalistic method. The informants in thisresearch are Headmaster, Senior High School (SMA) Negeri 1 Tanjung Tiram Batu Bara Regency, ThreeTeachers Counseling Guidance (counselor ) Students of class X, XI, and XII, and Guardians Class X, XI,and XII data obtained from two sources are primary data sources and secondary data sources. With datacollection techniques through observation, interviews and documentation, as for data analysis techniquesperformed by data reduction (data collection), presentation of data, and conclusions. To ensure the validityof the data, the researcher uses triangulation technique, triangulation is defined as a data aggregationtechnique that combines from various data collection techniques and data sources that already exist.